Feeding of bluefin tuna: Experiences in Japan and Spain - Norita T. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
This paper summarizes the research on feeding the Pacific Bluefin Tuna (PBFT), Thunnus thynnus orientalis, carried out at Kinki University (Japan), together with the work in Spain from 1995 on the Atlantic Bluefin Tuna (ABFT), Thunnus thynnus thynnus, at the private company Tuna Farms of Mediterraneo S.L. (TFM). Results on growth and feeding parameters obtained by the utilisation of several raw fish and moist pellets as food for the on-growing of bluefin tuna are presented.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)